Improvements of Decision Support Systems for Public Administrations via a Mechanism of Co-creation of Value - Tindara Abbate; Clara Bassano; Giuseppe D’Aniello; Sergio Miranda; Mirko Perano; Paolo Piciocchi; Luigi Rarità (Complex Systems Informatics and Modeling Quarterly)
This paper focuses on a possible improvement of knowledge-based decision support systems for human resource management within Public Administrations, using a co-creation of value’s mechanism, according to the Service-Dominant Logic (SDL) paradigm. In particular, it applies ontology-driven data entry procedures to trigger the cooperation between the Public Administration itself and its employees. Advantages in such sense are evident: constraining the data entry process by means of the term definition ontology improves the quality of gathered data, thus reducing potential mismatching problems and allowing a suitable skill gap analysis among real and ideal workers competence profiles. The procedure foresees the following steps: analyzing organograms and job descriptions; modelling Knowledge, Skills and Attitudes (KSA) for job descriptions; transforming KSAs of job descriptions into a standard-based model with integrations of other characteristics; extracting information from Curricula Vitae according to the selected model; comparing profiles and roles played by the employees.